Design and fabricating of an orthotic insole by using Kinect® XBOX gaming sensor scanner and 3D printer - Burhan, Mohd Hafiz (2015)
This project is to design and fabricate of an orthotic insole by using Kinect® XBOX 360 gaming sensor scanner and 3D printer. In order to fulfill medical requirement, it was invented to help medical field to overcome their problem of high 3D scanner cost, handcrafted fabrication, inventory problem, and long fabrication time. In term of process, author had proven the potential of Kinect® XBOX 360 gaming sensor as a 3D scanner, CAD as the method of the orthotic insole design, and Additive Manufacturing as the fabrication technique. In literature review, author had made deeply research in conventional orthotic insole fabrication which begins with plaster casting of the patient’s foot, followed by handcrafted orthotic insole design until the fabrication process. Author also had made visitation to Rehabilitation Hospital Cheras for data procurement regarding orthotic insole design and fabrication processes. In analytical phase, author had done calculation for the accuracy of the Kinect® XBOX 360 gaming sensor and the results shows Kinect® XBOX 360 device is capable of producing 3D reconstructed geometry with the maximum and minimum error of 3.78% (2.78mm) and 1.74% (0.46mm) respectively. Besides, the higher the scanned model dimension, the less error can be achieved based on the complexity of the scanned model. The orthotic insole design process had been done by using Autodesk Meshmixer 2.6 and Solidworks 2014 software with Rehabilitation Hospital Cheras as the main reference in design process. Fabrication of the orthotic insole had been made by using Flashforge 3D printer and Filaflex (TPE) filament as the material of the orthotic insole. For validation of the fabricated orthotic insole, author had conducted form, fit, and function test. As the result, the fabricated insole design produced 0.29mm RMS error compared to designed dimension. Functionality of the orthotic insole had been justified by conducting the foot pressure scan and the results had proven the fabricated insole is capable of reducing the pressure especially in metatarsal area. Furthermore, the fabricated insole was fit very well on the candidate’s foot.